OPTIMIZING COLLABORATIVE LEARNING: USING GOOGLE CLASSROOM IN BUSINESS ENGLISH CORRESPONDENCE CLASS - Subandoro, Philipus Suryo; Sulindra, Eric (VOCATIO : Jurnal Ilmiah Ilmu Administrasi dan Sekretari, 2018)
The recent learning trend has been put into practice collaboratively with so many aspects belonging to the core curriculum itself, such as Information Technology with its popular approach to collaborative learning. The study applied Google Classroom to the collaborative learning to maximize the learning in the classroom practice. The learning approach used is collaborative learning. The students utilized the collaborative features in Google Classroom to go beyond the limit of conventional learning such as time, space, and distance. The participants were the students taking English Business Correspondence Class of Widya Mandala Secretarial Academy Surabaya, Indonesia. The research found that Google Classroom was proven a supportive learning management system according to the students. Moreover, Google Classroom were proven useful to foster the process of writing process, during the revision stages. To sum up, Google Classroom were felt by the students to be the answer of ‘mobility in learning’ and to speed up the learning process, beyond time and spaces.